Inovasi Mahasiswa Kuliah Kerja Nyata Dalam Membuat Taman Baca di Situs Sejarah SMK Stannia Manggar Belitung Timur Untuk Menarik Wisatawan - Taufiq, Muhammad (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2024)
The reading gardenas a place where individuals can read and borrow books without cost or at an affordable price, becomes a center of education and culture that provides access to literature and knowledge. Students of the Practical Work (KKN) at Stannia Manggar Senior High School, Belitung East, have successfully initiated an innovation, namely the establishment of a library in a historical site. This research aims to analyze the social and cultural impact of this innovation in an effort to attract tourists. Through qualitative methods, this research found that the library not only functions as a reading space but also serves as a center for information on local history and a public interaction space for the community. This innovation has great potential to preserve cultural values, increase awareness of the importance of history, and develop tourism potential in the area.